What Is Your Diagnosis? - Inakanti, Y; Kumar, S (Nepal Journal of Dermatology, Venereology & Leprology, 2016)
<!–[if gte mso 9]> 800x600 <![endif]–> Seborrhoeic keratosis is slow-growing, sharply demarcated tumour with a fissured or pitted surface. Its surface may have a thin greasy scale. It is benign tumour of external ear originating from proliferative epithelial cells. Its most common site ranges from the retro auricular region to the helical rim. We present a female patient aged 62 years with a localized solitary seborrhoeic keratosis of left ear. Report of Unusual case of seborrhoeic keratosis. DOI: http://dx.doi.org/10.3126/njdvl.v12i1.10605 Nepal Journal of Dermatology, Venereology & Leprology Vol.12(1) 2014 pp.56-59 <!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Calibri","sans-serif"; –> <!–[endif] –>